2013
DOI: 10.1371/journal.pone.0069287
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rate and Tissue Localization of Murine IL-12p40-Producing Monocyte-Derived CD103+ Lung Dendritic Cells during Pulmonary Tuberculosis

Abstract: Non-hematopoietic cells, including lung epithelial cells, influence host immune responses. By co-culturing primary alveolar epithelial cells and monocytes from naïve donor mice, we show that alveolar epithelial cells support monocyte survival and differentiation in vitro, suggesting a role for non-hematopoietic cells in monocyte differentiation during the steady state in vivo. CD103+ dendritic cells (αE-DC) are present at mucosal surfaces. Using a murine primary monocyte adoptive transfer model, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Mouse lung DCs contain two major subpopulations: CD103+ CD11b low (or CD11b-negative) DCs and CD103-negative CD11b high DCs (4143). CD103+ DCs produce IL-12 and IFN-γ (4446) and predominantly elicit Th1 and Th17 responses (47), whereas CD11b high DCs primarily provoke a Th2 response (47, 48). We found that hyperoxic exposure was associated with an increase in lung CD103+, MHCII hi , CD86 hi DCs, a population of cells which was further increased upon viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse lung DCs contain two major subpopulations: CD103+ CD11b low (or CD11b-negative) DCs and CD103-negative CD11b high DCs (4143). CD103+ DCs produce IL-12 and IFN-γ (4446) and predominantly elicit Th1 and Th17 responses (47), whereas CD11b high DCs primarily provoke a Th2 response (47, 48). We found that hyperoxic exposure was associated with an increase in lung CD103+, MHCII hi , CD86 hi DCs, a population of cells which was further increased upon viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] In vivo, the expression of IL-23α is enhanced in PBMCs in nonhuman primates at the early stage of mycobacteria infection; later, its expression decreases to the normal level. 50 Moreover, levels of IL-12p40, one subunit of IL-23, are higher in the serum of TB patients than in HCs and decrease after anti-TB treatments. 48,50 IL-23 could mediate its effects on both innate and adaptive arms of the immune system that express the IL-23R.…”
Section: Interleukin-21mentioning
confidence: 99%
“…50 Moreover, levels of IL-12p40, one subunit of IL-23, are higher in the serum of TB patients than in HCs and decrease after anti-TB treatments. 48,50 IL-23 could mediate its effects on both innate and adaptive arms of the immune system that express the IL-23R. 48 Th17 cells are the representative T-cell subset that vigorously responds to IL-23.…”
Section: Interleukin-21mentioning
confidence: 99%
“…þ DCs are present exclusively in the lung airways and parenchyma after Mtb infection and are considered lung resident DCs, with migratory capacity to the draining lymph node (GeurtsvanKessel et al 2008;Geissmann et al 2010;Guilliams et al 2013b;Leepiyasakulchai et al 2013;Anderson et al 2014). cDCs and CD103 þ cDCs represent a functionally and phenotypically distinct pulmonary DC subset after Mtb infection and produce predominantly IL-12/ 23p40 (Mayer- Barber et al 2011;Leepiyasakulchai et al 2013).…”
Section: Identifying Myeloid Subset Diversity In Vivomentioning
confidence: 99%
“…cDCs and CD103 þ cDCs represent a functionally and phenotypically distinct pulmonary DC subset after Mtb infection and produce predominantly IL-12/ 23p40 (Mayer- Barber et al 2011;Leepiyasakulchai et al 2013). They express all the classical DC surface molecules (high levels of major histocompatibility complex class II (MHC-II), CD80, and CD86) as well as additional markers associated with antigen presentation and antigen-presenting cell (APC)-T-cell interactions, such as CD40, CD70, DEC-205, CD83, and PD-L2 (Mayer- Barber et al 2011;KD MayerBarber, unpubl.…”
Section: Identifying Myeloid Subset Diversity In Vivomentioning
confidence: 99%